Home-based physical activity in patients with type 2 diabetes mellitus: a scoping review - Mustapa, Nurul Amirah; Justine, Maria; Latir, Aliff Abdul; Manaf, Haidzir (2021)
To promote optimal healthcare delivery in type 2 diabetes mellitus (T2DM) following the outbreak of coronavirus disease 2019, adopting home-based physical activity (PA) is being seriously considered. Therefore, this study aims to outline the characteristics of exercise protocols for home-based PA and the challenges and limitations in implementing home-based PA in patients with T2DM. This scoping review was carried out by identifying eligible studies in six different databases (Scopus, Cochrane Library, SpringerLink, ProQuest, Science Direct, and Google Scholar). The keywords used in the search strategies were: home-based physical activity, home-based exercise therapy, home-based physical exercise, home-based exercise, home-based exercise training, diabetes mellitus, and T2DM. Two reviewers independently screened all full-text articles to find articles that met the eligibility requirements. A total of 443 articles were identified in the search. Approximately 342 articles were excluded by screening titles and abstracts, which led to the selection of 44 articles relevant to the current study. Further screening of the full-text led to the subsequent removal of 34 other articles, leading to 10 studies that were eligible for data extraction. This review suggested that the exercise protocols for home-based PA include resistance exercise using free weight and own body weight with a frequency of two to three sessions per week at moderate intensity, along with aerobic exercise (particularly walking) with a frequency of three to five times per week at moderate intensity. A combination of resistance and aerobic exercise showed more significant benefits of PA in patients with T2DM. More studies regarding home-based PA in T2DM patients with metabolic disorders are warranted.